2019
DOI: 10.1029/2018wr024322
|View full text |Cite
|
Sign up to set email alerts
|

Advective Transport in Discrete Fracture Networks With Connected and Disconnected Textures Representing Internal Aperture Variability

Abstract: Flow and transport in three‐dimensional discrete fracture networks with internal variability in aperture and permeability are investigated using a numerical model. The analysis is conducted for three different texture types representing internal variability considering various correlation lengths and for an increase in domain size corresponding to an increase in network complexity. Internal variability in discrete fracture networks generally increases median travel times and delays arrival of bulk mass transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 57 publications
(101 reference statements)
1
56
0
Order By: Relevance
“…The fracture internal aperture variability is a source of uncertainty due to difficulties in field measurement of fracture roughness or the aperture fields. For theoretical and numerical studies, correlated multivariant Gaussian, lognormal, and fractal fields are often used to describe the fracture aperture variability (Frampton et al, 2019; Huang et al, 2019). In this study, we use the spatially correlated lognormal fields to represent the fracture internal aperture variability, which is in analogy to previous studies (e.g., Frampton et al, 2019) and is partially supported by laboratory measurement data for rock fracture apertures (e.g., Pyrak‐Nolte et al, 1997).…”
Section: Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The fracture internal aperture variability is a source of uncertainty due to difficulties in field measurement of fracture roughness or the aperture fields. For theoretical and numerical studies, correlated multivariant Gaussian, lognormal, and fractal fields are often used to describe the fracture aperture variability (Frampton et al, 2019; Huang et al, 2019). In this study, we use the spatially correlated lognormal fields to represent the fracture internal aperture variability, which is in analogy to previous studies (e.g., Frampton et al, 2019) and is partially supported by laboratory measurement data for rock fracture apertures (e.g., Pyrak‐Nolte et al, 1997).…”
Section: Models and Methodsmentioning
confidence: 99%
“…For theoretical and numerical studies, correlated multivariant Gaussian, lognormal, and fractal fields are often used to describe the fracture aperture variability (Frampton et al, 2019; Huang et al, 2019). In this study, we use the spatially correlated lognormal fields to represent the fracture internal aperture variability, which is in analogy to previous studies (e.g., Frampton et al, 2019) and is partially supported by laboratory measurement data for rock fracture apertures (e.g., Pyrak‐Nolte et al, 1997). Therefore, the mean transmissivity of each discrete fracture is semicorrelated to its size and follows the power law, while the internal aperture field for each fracture is a correlated lognormal field with assigned mean transmissivity ( semicorrelated to its size), variance, and correlation length.…”
Section: Models and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fracture apertures are uniform within each fracture and equal to b = 10 −4 m, which is a physically reasonable aperture value for a 1 m fracture in crystalline rock under assumptions of a positively correlated power law relationship between fracture size and radius (Svensk Kärnbränslehantering, 2010). While it is well documented that aperture variability leads to local dispersion within an individual fracture (Boutt et al, 2006;Cardenas et al, 2007;Detwiler et al, 2000;Kang et al, 2016), recent high-fidelity DFN simulations in fracture networks have shown that aperture variability does not significantly influence behavior at the network scale, BTC (Frampton et al, 2019;Makedonska et al, 2016), or effective permeability (de Dreuzy et al, 2012), except at high aperture variance or long correlation lengths relative to the domain size. Rather, it is the fracture network structure that controls flow and transport behavior.…”
Section: Discrete Fracture Network Simulations: Particle Travel Time mentioning
confidence: 99%
“…At the scale of individual fractures, their orientations (Rubin & Buddemeier, 1996) and apertures (Bogdanov et al., 2007; de Dreuzy et al., 2002; Frampton & Cvetkovic, 2010; Hyman et al., 2016; Joyce et al., 2014; Wellman et al., 2009) can also cause variations of the flow field. At the even smaller scale within a single fracture, aperture variability/roughness is well known to lead to flow channelization (Boutt et al., 2006; Cardenas et al., 2007; Detwiler et al., 2000; de Dreuzy et al., 2012; Frampton et al., 2019; Kang et al., 2016; Makedonska et al., 2016; Méheust & Schmittbuhl, 2000, 2001). In summation, the integration of these multiple scales renders linking structural attributes to the formation of flow channels a particularly challenging task.…”
Section: Introductionmentioning
confidence: 99%